2019
DOI: 10.4314/acsj.v27i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of silica nanoparticles on groundnut bruchid, Caryedon serratus (Olivier) (Coleoptera, Bruchidae)

Abstract: In Senegal, post-harvest losses caused by groundnut bruchid, Caryedon serratus, are detrimental to farmers and affect national economy. The objectivie of this study was to investigate the effectiveness of silica nanoparticles against C. serratus. Silica nanoparticles were synthesized by reverse microemulsion and different concentrations (0.17, 0.33, 0.67 and 1.7 mg kg-1) were tested on mortality and fecundity of C. serratus. Result showed that silica nanoparticles had high toxicity on C. serratus adults. Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nanoparticles toxicity has been demonstrated against many insects such as Sitophilus oryzae (Debnath et al, 2011), mosquitoes, including Anopheles stephensi Liston, Aedes aegypti Linnaeus and Culex quinquefasciatus Say (Barik et al, 2012), cotton leafworm, Spodoptera littoralis (El-bendary and El-Helaly, 2013) and the cowpea seed beetle, Callosobruchus maculatus (F.) (Rouhani et al, 2013 andArumugam et al, 2016). The insecticidal activity of nanosilica was also confirmed by Ziaee and Ganji (2016); Diagne et al (2019);Rouhani et al (2019); Haroun et al (2020) and Salem (2020) against Rhythopertha dominica F., Tribolium confusum Jacquelin du Val., Caryedon serratus (Olivier), Tribolium castaneum Herbst., C. maculatus F., and Sitophilus granarius (L.).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles toxicity has been demonstrated against many insects such as Sitophilus oryzae (Debnath et al, 2011), mosquitoes, including Anopheles stephensi Liston, Aedes aegypti Linnaeus and Culex quinquefasciatus Say (Barik et al, 2012), cotton leafworm, Spodoptera littoralis (El-bendary and El-Helaly, 2013) and the cowpea seed beetle, Callosobruchus maculatus (F.) (Rouhani et al, 2013 andArumugam et al, 2016). The insecticidal activity of nanosilica was also confirmed by Ziaee and Ganji (2016); Diagne et al (2019);Rouhani et al (2019); Haroun et al (2020) and Salem (2020) against Rhythopertha dominica F., Tribolium confusum Jacquelin du Val., Caryedon serratus (Olivier), Tribolium castaneum Herbst., C. maculatus F., and Sitophilus granarius (L.).…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles in combination with plant oil Ricinus communis showed 67.89% repellency at 15% concentration and 28.31% repellency at the same concentration in combination with Citrus paradise oil against T. castaneum (Shahzadi et al, 2019). SiO 2 nanoparticles showed a strong defensive response against Caryedon serratus in groundnut at 0.67 mg/kg and 1.7 mg/kg, and it was observed that mortality increased with time of exposure (Diagne et al, 2019). Inorganic nanosilica killed 50% of adults T. castaneum at 0.90% concentration after 10 days of treatment (Khalil, 2019).…”
Section: Silicon Dioxide Nanoparticles (Sio 2 Nps)mentioning
confidence: 99%
“…Inorganic nanosilica killed 50% of adults T. castaneum at 0.90% concentration after 10 days of treatment (Khalil, 2019). SiO2 nanoparticles act as a strong defensive tool against Caryedon serratus in groundnut at 0.67 mg/kg and 1.7 mg/kg, and mortality increased with time of exposure (Diagne et al, 2019). Rouhani et al (2019) proved that silica nanoparticles (SNPs) are highly effective against S. granarius causing 100% mortality after 2 weeks.…”
Section: Silicon Dioxide Nanoparticles (Sio 2 Nps)mentioning
confidence: 99%